Assessing the needs of parents of "at-risk" children in residential care : towards the development of a parent support programme - Gorvalla, Shereen (Department of Social Development, 2024)
The research study that the researcher was engaged in, attempted to gather, present and analyse the needs and assess the present level of functioning of parents of"at-risk" children in residential care. An exploratory study was conducted at a non-profit welfare organisation, a residential institution in Athlone. The importance of the study was an attempt to make a contribution to the understanding that if reunification is an attempt to reunite the child back with it's family then one cannot work with children in isolation from the parents. Traditionally, parents were viewed as part of the problem rather than being part of the solution, therefore, this study also attempts to bridge that gap and looks at assessing and addressing the needs of the parents of children in residential care. The study used the semi-structured interview method and focus-group sessions. There were ten respondents interviewed at their homes and of the ten only seven responded to the focus-group sessions. The data collected was used to generate themes and subcategories. The conclusions that the study arrived at, are that, it is important for parents to be included from the very beginning and continuous assessment of the needs of families be made. The study also concludes that there is a need to assist not only the children but the parents with skills to cope with day-to-day situations. Therefore, the study further highlighted the need for an effective support programme for parents, to give vent to their fears and expectations for themselves and their children. I would like to note that due to the limited nature of methodology, time and scope of the study, the conclusions arrived at in this study should not be generalised beyond the confines of the study, as the residential agency cannot be representative of all the residential facilities in Cape Town.